Online self-regulation strategies of university students - YILMAZ VİRLAN, AYŞE (My University, 2021)
Education is a part of life itself, so is learning-to-learn regardless of age, time and place (Samancı & Ocakcı, 2017). We need to acquire several essential skills and competencies at various levels to cope with modern life. Yet, especially after the burst out of COVID-19 pandemics it was realized that improvement of knowledge and skills professional and daily life wise from childhood to adulthood is sine qua non (Tedmem, 2020). These skills, which consist of cognitive and metacognitive learning strategies, largely have been neglected in analyses of issues surrounding lifelong learning and in policy development (Cornford, 2002). Self-regulation is an important learning strategy in developing life-long learning skills. It focuses on the learner planning his own learning process, making adjustments when necessary, and self-motivation throughout the training process. Zimmerman (2002) defines the characteristics of self-regulated learners as individuals who are aware of the difficulties and limitations that they can face in their own learning, and who can use strategies that are appropriate for these goals and motivate themselves throughout the learning process. As the online learning environment is characterized with autonomy, self-regulation becomes a critical factor for success in online learning (Barnard, et al., 2009). Gaining self-regulation skills for students in online learning environments is quite different from face-to-face learning settings as they require dynamic learning interfaces (Yavuzalp & Özdemir, 2020). To the best of the researchers` knowledge the role of self-regulatory skills in the online learning environment is limited in our country and has not received the same attention as it does in the traditional faceto-face environment (Barnard, et al., 2009; Yavuzalp & Özdemir, 2020). Moreover, the findings of studies also show that the self-regulation skills of higher education students is a problematic issue (Lonka and LindblomYlänne, 1996; Virtanen and Nevgi, 2010), and that they also have unrealistic conceptions of their use of learning strategies (Winne & Jamieson-Noel, 2003). The high challenging nature of courses offered at higher education and their way of delivery (Ketonen et al, 2016; Ganda & Boruchovitch, 2015; Basso et al, 2013) could hinder effective and efficient lifelong learning of even highly motivated and well-selected university entrants due to their lack of or limited self-regulatory skills. For this reason, the aim of this study is to identify the perceived self-regulation level of tertiary students.
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Social Sciences and Humanities; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Lifelong learning; online learning; self-regulation strategies; socioeconomic status